Estudo do comportamento dinâmico de pontes rodoviárias mediante avaliação da deterioração progressiva do pavimento - Silva, Ana Célia Soares da (2020)
Highway bridges are usually subjected to random dynamic actions of variable magnitude due to vehicles convoys crossing on the bridge pavement deck along their service life. These dynamic actions can generate the nucleation of fractures or even their propagation on the bridge deck structure. On the other hand, the deteriorated road surface condition of the asphalt pavement represents a key issue to the significant increase of the displacements and stresses values on the highway bridge decks. Therefore, this research work aims to develop an analysis methodology to evaluate the dynamic structural response of a steel-concrete composite highway bridge (displacements and stresses), including the dynamic actions due to vehicles convoys traveling on the irregular pavement and the effect of the road progressive deterioration over time. This way, the structural model investigated in the present study corresponds to a typical steel-concrete composite highway bridge deck, with straight axis and spanning of 40.0 m. The structural system is constituted by four composite girders and a 0.225 m thick concrete slab. In this investigation, the numerical model developed for the dynamic analysis of the steel-concrete composite bridge adopted the usual mesh refinement techniques present in Finite Element Method (FEM) simulations implemented in the ANSYS program. The conclusions of this research work indicate that the dynamic structural response of the analyzed bridge, in terms of the values of displacements and stresses, and considering the deteriorated road pavement, underwent important amplifications, in the order of 3 to 8 times higher, when compared to the situation without deterioration. This fact means that the effect of the progressive deterioration of the road pavement, over time, is relevant and needs to be considered in the dynamic analysis and design of structural road bridge systems.